Proyecto de factibilidad para la creación de una empresa de servicio de estudio de seguridad y salud ocupacional para las empresas privadas de la ciudad de Loja - Coronel Hernández, Mario Alberto (2015)
The project that appears to perform a feasibility study for setting up a company Service Study Occupational Safety and Health for Private Enterprises in the city of Loja, which is comprised of four major studies such as: Market Research, Technical Study, Organizational Study, Finance and Financial Evaluation Study. The implementation of a business service company study Occupational Safety and Health for private companies of the city of Loja allowed the application of different methods and techniques that research allows as the inductive method which we obtained general conclusions from particular premises, this method is applied in the study's findings to make recommendations as alternative proposals, the Deductive Method considers the conclusion is implicit within the premises and allowed to know the reality of operation and management of a service company Studies Occupational Safety and Health, Descriptive method in the project feasibility would generally applied to the current economic, social reality experienced by our city, which allowed us to develop the research problem in the area of occupational safety and health and finally the Statistical Method, which I applied in the survey, owners of private companies that require service study Occupational Safety and Health of the city of Loja and interview that applied to the responsible Security Technical and Occupational Health MRL was performed, in order to obtain information, analyze it, work it, and interpret the specific data for the feasibility study and project creation. In the market study in the province of Loja, it is determined that the project can and should be performed by the results obtained in the analysis of demand, supply and levels of welcome and acceptance of the company. The unmet demand reflects the potential that exists in the province cited for this service market with the following results: For the first year of life of the project is unmet demand 84 companies needing Research Department Occupational Safety and Health, which the company will serve 9.52%, i.e. 8 Enterprises. The service process demands the use of appropriate measuring equipment, which will guarantee for a quality service at a relatively low price The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 13.953,19 which indicates that the project or investment is suitable. For this project, the IRR is 14,89%, this being satisfactory value for the project, the time required to recover the original investment would be 5 years and 0,21 months, for this project , the sensitivity values are less than one therefore does not affect changes in project costs and increased revenue decreased 5,15% and a 22.33% , respectively , ie the project is not sensitive to these changes